Phenolic and Flavonoid Compounds from Leaves and Branches of Schotia brachypetala for the Development of Biofungicide for Wood Protection - Mohamed Zidan Salem; Nader A. EL-Shanhorey; Nashwa H. Mohamed; Abeer A. Mohamed (BioResources)
The extracts of Schotia brachypetala were tested against the molecularly identified fungi Alternaria alternata, Botrytis cinerea, and Fusarium oxysporum, which cause early blight of tomatoes, gray mold of cucumber immature fruits, and Fusarium wilt, respectively. Leaves and branches of S. brachypetala were extracted using acetone and bio-assayed for their antifungal activity at 2%, 4%, and 6% when applied to white mulberry wood samples. Using high-performance liquid chromatography analysis, the most abundant compounds in leaf extract were kaempferol (37900 µg/g extract) and gallic acid (7480 µg/g extract), and in branch extract were gallic acid (3120 µg/g extract) and chlorogenic acid (1320 µg/g extract). By increasing the extract concentration to 6%, the percentage inhibition of fungal mycelial was significantly increased compared to the positive (Cure-M) and negative control samples. This study indicates that extracts from leaves and branches of S. brachypetala can be effective as bio-based agents in wood protection and that they can prevent the growth of pathogenic fungi.